Creatine supplementation and performance during off-season training in female soccer players - Larson, D. E.; Hunter, G. R.; Trowbridge, C. A.; Turk, J. C.; Harbin, P. A.; Torman, S. L. (Medicine & Science in Sports & Exercise, 1998)
Creatine monohydrate was supplemented for 13 weeks in female collegiate soccer players during a period of training. Two groups of seven players were formed, one receiving a placebo, the other Cr supplementation (7.5 gm twice a day for the first week and then 5 gm per day). After 3-5 weeks the creatine group had significantly improved performances in a shuttle run and bench press over those demonstrated by the placebo group. There was no further improvement over the remainder of the study. Implication. Creatine supplementation provides a boost to female anaerobic work within a few weeks and then its effects remain stable.